Molecular and morphological delineation of Caloglossa beccarii and related species (Delesseriaceae, Rhodophyta). Issue 6 (1st November 2016) - Kamiya, Mitsunobu; West, John A.; Karsten, Ulf; Ganesan, E. K.
Abstract: Systematic studies on the closely related red algal species of Caloglossa, C. beccarii, C. fluviatilis and C. stipitata, were conducted because the morphological and phylogenetic distinction of the three species was not resolved previously. The large-subunit ribosomal DNA or rbc L gene analyses revealed that specimens from Indian freshwater rivers and German and Ukrainian freshwater aquaria form a clade with C. fluviatilis from the Panama Canal, and this clade is distinct from C. beccarii and C. stipitata . Caloglossa fluviatilis was morphologically distinguished from the other two species by the smaller number of cells in a second-order row at the internode, the narrower blade, smaller number of rhizoids at the node, and fewer rhizoids produced from wing cells. The number of rhizoids at the node and the ratio of internodal blade length to upper blade width were useful to delineate the three species. Low-molecular-weight carbohydrate analyses revealed that strains from freshwater habitats as well as brackish habitats contain both the C-6 polyol mannitol and the heteroside digeneaside. The present study confirmed the distinctness of the three species, and this is the first report of C. fluviatilis from other than the type locality.